The Role of Full or Partial Mediation of Intention between Patriotism, Trust, Government Support through Structural Equation Modeling (SEM) Effect on Actual Purchase toward Malaysia Brand - Jamal Mohammed Esmail Alekam; Nik Kamariah Nik Mat; Farouk Djermani (International Journal of Supply Chain Management, 2017)
The aim of this paper is to investigate the antecedents of actual purchase on Malaysian brand, Patriotism, trust, government support and intention. Moreover, the research framework was built and tested based on the Theory of Planned Behavior. The research instrument consisted of 39 items, patriotism 10, trust 8, government support 8, intention 8, and actual purchase 5, adapted from previous studies. Questionnaires were distributed to 300 respondents in Kedah (Jitra, Changloon, Simpang Kuala and Sungai Petani (170), Penang ( Kepala Batas (40)),Perlis (Arau (90) with 202 respondents, consequently this representing 67.3% response rate. The data were analyzed using Structural equation modelling (SEM). This study has established seven direct and indirect hypotheses. The findings of the study highlight that purchase intentions has significant relationship with trust,(Estimate 0,382, C.R.2,792, p-value 0,005),as well as actual purchase has a direct significant relationship with patriotism (Estimate 0,298, C.R. 2,331, p-value 0,02 ), actual purchase has significant relationship with purchase intention (Estimate 0,7, C.R. 6,206, p-value 0.000*** ), lastly government support has significant relationship with purchase intention(Estimate 0,287, C.R. 3,079, p-value 0,002 ).Meanwhile, full mediating between trust and actual purchase. Finally this result of this study will deepen the understanding of Malaysian customers behavior toward its own products.